Hellenistic and Roman Terracottas: Mediterranean Networks and Cyprus - Jaimee Uhlenbrock (Les Carnets de l’ACoSt)
The Archaeological Research Unit of the University of Cyprus in Nicosia was the site of a 3-day conference dedicated to Hellenistic and Roman terracottas that was organized by Giorgos Papantoniou, Demetrios Michaelides, and Maria Dikomitou-Eliadou. I was the discussant. The conference was held within the framework of a research project funded by the Anastasios G. Leventis Foundation via the University of Cyprus. The project aimed to establish a more concrete scholarly discussion on the study of Hellenistic and Roman terracottas in relation to a large corpus of Hellenistic and Roman terracottas that was brought to light during recent excavations at the “House of Orpheus” at Nea Paphos. A particular focus was placed on the integration of different analytical approaches for the study of these figurines and the relationships that these might have had with Hellenistic and Roman terracottas from other sites around the Mediterranean. The convenors of the conference Giorgos Papantoniou, Demetrios Michaelides, and Maria Dikomitou-Eliadou hoped that the continuing and changing patterns of production, distribution and function of Cypriot terracottas would be clarified as a result of discussions that treated the interplay between local structures and incoming Ptolemaic and Roman socio-political and socio-cultural impositions.